Smart money smart kids : raising the next generation to win with money - Ramsey, Dave (Lampo Press, 2014)
"Dave Ramsey and Rachel Cruze teach parents how to raise money-smart kids in a debt-filled world. In Smart Money Smart Kids, financial expert and best-selling author Dave Ramsey and his daughter Rachel Cruze equip parents to teach their children how to win with money. Starting with the basics like working, spending, saving, and giving, and moving into more challenging issues like avoiding debt for life, paying cash for college, and battling discontentment, Dave and Rachel present a no-nonsense, common-sense approach for changing your family tree"--